Upregulation of miR-21 in cisplatin resistant ovarian cancer via JNK-1/c-Jun pathway. - Ileabett M Echevarría-Vargas; Fatma Valiyeva; Pablo E Vivas-Mejía (PLoS ONE)
Cisplatin has been the most accepted drug for the treatment of ovarian cancer for almost 40 years. Although the majority of patients with ovarian cancer respond to front-line platinum combination chemotherapy, many patients will develop cisplatin-resistance disease, which is extremely rapid and fatal. Although various mechanisms of cisplatin resistance have been postulated, the key molecules involved in such resistance have not been identified. MiRNAs are endogenously expressed small non-coding RNAs, which are evolutionarily conserved and function as post-transcriptional regulators of gene expression. Dysregulation of miRNAs have been associated with cancer initiation, progression and drug resistance. The oncogenic miRNA-21, one of the best-studied miRNAs, is upregulated in almost all human cancers. However, the regulation of miR-21 in cisplatin resistant ovarian cancer cells has not been assessed. In this study, we measured the miR-21 expression by real-time PCR and found upregulation of miR-21 in cisplatin resistant compared with cisplatin sensitive ovarian cancer cells. Chromatin immunoprecipitation studies demonstrated the association of the c-Jun transcription factor to the pri-mir-21 DNA promoter regions. Blocking the JNK-1, the major activator of c-Jun phosphorylation, reduced the expression of pre-mir-21 and increased the expression of its well-known target gene, PDCD4. Overexpression of miR-21 in cisplatin sensitive cells decreased PDCD4 levels and increased cell proliferation. Finally, targeting miR-21 reduced cell growth, proliferation and invasion of cisplatin resistant ovarian cancer cells. These results suggest that the JNK-1/c-Jun/miR-21 pathway contributes to the cisplatin resistance of ovarian cancer cells and demonstrated that miR-21 is a plausible target to overcome cisplatin resistance.